Pelaksanaan UUD 1945 tentang Negara Mencerdaskan Kehidupan Bangsa sebagai Amanat Konstitusi - Anak Agung Sagung Laksmi Dewi; Anak Agung Ngurah Adhi Wibisana (Verdict: Journal of Law Science, 2026)
The constitutional mandate in the 1945 Constitution stating that “the state shall educate the life of the nation” represents the state’s responsibility in the provision of education and the development of human resources. This article examines three research problems: (1) what legal evidence demonstrates that the state has an obligation to educate the life of the nation; (2) how the government implements Article 31 of the 1945 Constitution; and (3) what legal consequences arise if the state fails to fulfill this constitutional mandate. The research employs a normative juridical approach using both the statute approach and the analytical approach through the examination of the constitution, legislation, and academic literature. The findings indicate that the state’s obligation to educate the life of the nation has a strong legal foundation, including Article 31 of the 1945 Constitution and various implementing laws. The government has undertaken numerous efforts through education budgeting, compulsory education policies, and the development of the national education system. However, shortcomings in implementation still occur, which result in legal consequences such as state responsibility, the potential for constitutional claims by citizens, and negative implications for human rights and social justice. This article concludes that the mandate of the 1945 Constitution must be translated into measurable and accountable policies so that the realization of “educating the life of the nation” is not merely symbolic.